2016
DOI: 10.5774/45-0-204
|View full text |Cite
|
Sign up to set email alerts
|

Some Syntactic Features of Relative Constructions in the Greek New Testament

Abstract: In the Greek New Testament, relative sentences that are introduced by relative pronouns alone, apart from the adverbial uses, are the most frequent subordinate sentence type. The research reported on in this paper aimed to investigate and describe a number of syntactic features of relative constructions in the Greek New Testament, taking account, among others, of some typological parameters that have been developed in the general linguistics literature for these constructions. The results indicate that relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The obtained core-cluster structures only represents a small spectrum of possible cluster masses, but could easily be extended to allow the formation of eight or more clusters. By confining the system to the formation of only four clusters, we found that the most likely, and experimentally observed, clusters are always present [14], and therefore found it satisfactory to keep to the formation of only four clusters.…”
Section: B Ementioning
confidence: 78%
See 1 more Smart Citation
“…The obtained core-cluster structures only represents a small spectrum of possible cluster masses, but could easily be extended to allow the formation of eight or more clusters. By confining the system to the formation of only four clusters, we found that the most likely, and experimentally observed, clusters are always present [14], and therefore found it satisfactory to keep to the formation of only four clusters.…”
Section: B Ementioning
confidence: 78%
“…where the parameter a is the diffuseness, V 0 is the potential depth, R 0 is the radius, and the parameter x indicates the relative contributions made by the Woods-Saxon and the cubic Woods-Saxon terms. The best-fit parameters which describes the cluster emission of actinide nuclei is given by [12][13][14]…”
mentioning
confidence: 99%
“…It is a research hotspot (Lyon & Montgomery, 2015) that this study intends to examine the interaction role of greenwash perceptions affecting green consumerism. Greenpeace (1997) conceptualizes greenwashing as a company's practice to mislead consumers for the sake of benefiting or falsely claiming eco‐friendly operations; Du Toit (2015) views greenwashing practices as impacting the company's reputation, stakeholders' financial performance, and an entire society. However, the paper considers greenwashing perception practices recognizable to consumers, such as perceiving a company's wrongful claim of greenness, incongruous environmental records, and overall shortfalls of environmental integrity.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“… As Du Toit’s (: 60) example (19b) makes clear, case is not always assigned by a constituent in the matrix clause in these three contexts, at least not in context (iii). Further research is needed on this issue. …”
mentioning
confidence: 90%
“…2 Ancient Greek headed relative clauses have been subject to a great number of studies, among which see Probert (2015) for Archaic Greek; Monteil (1963), Adams (1972), Brunel (1977) for Archaic and Classical Greek;Biraud (1980), Chanet (1980), Pieters (1980), Rijksbaron (1981), Stelter (2004: 28-139), Perna (2013a;2013b), Luj an (2014) for Classical Greek; Vierros (2003) for Early Post-classical Greek; Kriki (2013) for Post-classical Greek; Du Toit (1986Toit ( , 2015Toit ( , 2016, Boyer (1988), Culy (1989), Petersen (2001) and Kirk (2012: 177-224) for New Testament Greek. 3 Fauconnier's (2014) study is concerned specifically with Classical Greek (V-IV BC).…”
Section: Introductionmentioning
confidence: 99%